2D drawing machine / Muhammad Yusof Abdul Rauf, Nurul Fatiha Mohmad Yusry & Muhammad Amirul Abdul Malik - Abdul Rauf, Muhammad Yusof; Mohmad Yusry, Nurul Fatiha; Abdul Malik, Muhammad Amirul (2019)
An artist robot that draws portraits like a human artist is presented in earlier in the year. This application concerns entertainment; it was developed at the PPRIME Institute in the ROBIOSS team and a patent was deposited for this invention in 2007. The "artist robot" draws every day the portraits of the visitors by using a camera and a pen attached to end-effector. Based on the specifications, the whole application is detailed. The drawing machine and its environment are described; and software engineering and image processing are discussed. Results illustrate the efficiency and the success of the drawing machine and an analysis of how the task is carried out is provided. Based on our research we found out that many people having problem when they want to drawing or writing something in their daily life. Hence some people just waste time with drawing ad writing that caused they feel bad when this work do. Besides, we also know that some people always do mistake when drawing or writing such as error in measurement o spelling. It will slow down the flow of their work because they must recheck their work and must make some correction. Thus, the main objective of our project are create a machine that can be used for writing and drawing that can make it easier for all work efficiently and more user-friendly with more innovative also to make improvement to that more useful for all future generations with systematic system